The Meaningful Writing Project : Learning, Teaching and Writing in Higher Education - Eodice, Michele, 1957-; Geller, Anne Ellen, 1969-; Lerner, Neal (Book collections on Project MUSE., 2016)
"Unprecedented look into the writing projects students find meaningful. The results of a three-year study consisting of surveys and interviews of seniors and faculty across three diverse institutions that consider the qualities of experiences, students' perceptions of their experiences, and analyze instructors' perspectives on assignment design/delivery "--Provided by publisher.